2015
DOI: 10.1111/ahg.12133
|View full text |Cite
|
Sign up to set email alerts
|

Hypovitaminosis D in a Young Lebanese Population: Effect of GC Gene Polymorphisms on Vitamin D and Vitamin D Binding Protein Levels

Abstract: Bioactive vitamin D is a steroid hormone transported in blood via the vitamin D binding protein (DBP). Our study aimed to investigate the vitamin D status in a young Lebanese population and study the association of hypovitaminosis with levels of DBP. Polymorphisms in the GC gene that encodes DBP were also screened. Blood samples were collected from 179 university students. Vitamin D status and DBP levels were assayed by enzyme-linked immunosorbent assay (ELISA). DNA was extracted from 128 participants, and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
(46 reference statements)
4
9
1
Order By: Relevance
“…Medlej-Hashim et al collected blood samples from 128 university students and found participants with genotypes rs4588 AA had higher concentrations of DBP in a young Lebanese population [44]. The result was similar to ours.…”
Section: Discussionsupporting
confidence: 86%
“…Medlej-Hashim et al collected blood samples from 128 university students and found participants with genotypes rs4588 AA had higher concentrations of DBP in a young Lebanese population [44]. The result was similar to ours.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, our results indicated that patients with schizophrenia, as well as the healthy ones, had a vitamin D deficiency, similar to previous studies [2,4,36,37,40,41]. Other studies conducted in Lebanon had shown a hypovitaminosis D in the healthy population [35,[42][43][44][45].…”
Section: Discussionsupporting
confidence: 91%
“…We couldn't detect any association between the total PANSS score and its three subscales with vitamin D deficiency (p>0.05). Lebanon has a high prevalence of 25(OH)-D deficiency in adults and older adults [23,24] however, data regarding vitamin D levels in psychiatric patients is still lacking. Therefore, the primary objective of this study was to compare the vitamin D status in schizophrenics to that of healthy controls; secondary objectives were to assess the…”
Section: Methodsmentioning
confidence: 99%
“…No differences in the VDBP concentrations were found using polyclonal antibody method [37] or the LC-MS/MS method [19, 38], though the ELISA method with a monoclonal antibody for VDBP may induce bias [3842]. Using an ELISA kit with a polyclonal antibody, we did not find a difference in the plasma VDBP concentrations between the subgroups of participants (Table 1 and Additional file 1: Table S1), nor was the VDBP concentration correlated with the plasma 25OHD concentration (Additional file 1: Table S3).…”
Section: Discussionmentioning
confidence: 99%